Effects of sulfated and non-sulfated β-glucan extracted from Agaricus brasiliensis in breast adenocarcinoma cells – MCF-7 - Baranoski, Adrivanio; Oliveira, Marcelo Tempesta; Semprebon, Simone Cristine; Niwa, Andressa Megumi; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mário Sérgio (Taylor & Francis, 2015)
The β-glucans (β-G) are polysaccharides produced by various organisms, and sulfation of β-G renders them more soluble. With the objective to assess the effects of sulfated and non-sulfated β-G extracted from Agaricus brasiliensis in MCF-7 cells, assays were used to evaluate cytotoxicity, genotoxicity, cell proliferation and mRNA expression. The sulfated and non-sulfated β-G showed dose-dependent cytotoxicity at concentrations of 5 and 10 μg/mL, by the MTT assay. However, only cytotoxicity was observed after 24 h by the Red Neutral test for sulfated β-G, with no genotoxicity for either β-G in comet assay. Proliferation was decreased only at 72 h at a concentration of 100 μg/mL of sulfated β-G. Treatment with 5 μg/mL of sulfated β-G for 6 h reduced the expression of pro-apoptotic genes and stress signaling genes, cell cycle arrest, damage and cell migration. The 5 μg/mL of non-sulfated β-G for 6 h reduced the expression of the stress response gene and signaling damage. These results indicate that the cytotoxicity in the MTT is not cell death, and that, in general, sulfated β-G have greater cytotoxicity compared to non-sulfated β-G.
Keywords: Cell proliferation; Cytotoxicity; Genotoxicity; RT-qPCR